Complex Permittivity and Predominance of Non-Overlapping Small-Polaron Tunneling Conduction Process in Copper Indium Selenide Compound - Singh, D (Walter de Gruyter GmbH, 2023)
This paper presents a study of the complex permittivity of n-Type copper indium selenide semiconductor compound at low temperatures down to-175 C. Alternating current with frequency varying between 20 Hz and 1 MHz is applied to the material in order to measure the dielectric constant and dielectric loss D is found to decrease with temperature and frequency, whereas D decreases with frequency and increases with temperature. The experimental data of agree with the expression = Am(,T), where the frequency exponent m(T), calculated through the relation m(T) = (ln / ln )T , shows a frequency and temperature dependence. The data are analyzed in light of existing theoretical models. © 2023 Walter de Gruyter GmbH, Berlin/Boston.